2022
DOI: 10.1080/10409289.2022.2056694
|View full text |Cite
|
Sign up to set email alerts
|

Meeting 24-hour movement behavior guidelines in young children: Improved quantity estimation and self-regulation

Abstract: Research findings: The present study examined the associations among meeting 24-hour movement behavior recommendations set by the World Health Organization (2019) and young children's self-regulation and quantity estimation skills in a sample of 123 children (n = 65 female; 4.9 ± 0.7 years) in mid-Michigan.Meeting screen time recommendations alone, meeting physical activity recommendations in combination with either sleep or screen time recommendations, meeting more recommendations overall, and being active mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 115 publications
0
14
0
Order By: Relevance
“…A total of 387,437 participants (49% of boys and 51% of girls) aged 3–18 years were included in this systematic review and meta-analysis, of which 11,768 were preschoolers (3–5 years; 3%), 76,928 (6–12 years; 20%) were children, and 298,741 (13–18 years; 77%) were adolescents. Twenty-six studies were conducted with preschoolers only, 8 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 13 studies with children only, 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 17 studies with adolescents only, 11 , 12 , 60 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 and 7 studies with both children and adolescents. 9 , 10 , 76 , 77 ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 387,437 participants (49% of boys and 51% of girls) aged 3–18 years were included in this systematic review and meta-analysis, of which 11,768 were preschoolers (3–5 years; 3%), 76,928 (6–12 years; 20%) were children, and 298,741 (13–18 years; 77%) were adolescents. Twenty-six studies were conducted with preschoolers only, 8 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 13 studies with children only, 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 17 studies with adolescents only, 11 , 12 , 60 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 and 7 studies with both children and adolescents. 9 , 10 , 76 , 77 ...…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the measurement of the 3 components of the 24-Hour Movement Guidelines, physical activity was obtained by device-based measures in 37 studies, 8 , 9 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 46 , 47 , 49 , 51 , 52 , 53 , 54 , 55 , 59 , 64 , 65 , 73 , 76 , 78 , 81 self-reported measures in 22 studies, 10 , 11 , 12 , 50 , 57 , 58 , 60 , 61 , 62 , 63 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 74 , 75 , 77 , 79 , 80 and parent-reported measures in 4 studies. 32 , 45 , ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Organizing the classroom schedule with a balance of sedentary and varied intensities of activity across the school day can facilitate young children's learning. Because short bouts (~10 mins) of vigorous "huff and puff" intensity activities can support children's attention and self-regulation (McGowan et al, 2020(McGowan et al, , 2021aMcGowan, Gerde, et al, 2022), teachers may consider planning vigorous movement opportunities to precede times of more sedentary lessons. For example, teachers might engage children in a vigorous music and dancing experience prior to sitting for their morning meeting, play a game in which children jump when they hear rhyming words to a poem before sitting for book reading, and engage in small group instruction after children have returned from outdoor play or the gymnasium.…”
Section: Build Opportunities For Movement Into Your Daily Schedulementioning
confidence: 99%
“…Since the pandemic, children's screen time with non‐educational content has dramatically increased as schools and extra‐curricular opportunities have moved online (Moore et al, 2020). A national study conducted in Canada identified that 83.5% of children exceed the national recommendations for screen time (Moore et al, 2020); in the United States, recent research found 75.6% of 4‐year‐olds exceeded screen time recommendations (McGowan et al, 2022). Half of the families surveyed by the Parents Together Foundation (2020) reported their child spends more than 6 hours with screens each day, primarily engaged in non‐educational e‐activities.…”
Section: Professional Recommendations and Potential Risks Of Screen Timementioning
confidence: 99%